Quantification of NG2‐positivity for the precise prediction of KMT2A gene rearrangements in childhood acute leukemia. Issue 2 (20th November 2020) - Zerkalenkova, Elena; Mikhaylova, Ekaterina; Lebedeva, Svetlana; Illarionova, Olga; Baidun, Liudmila; Kashpor, Svetlana; Osipova, Elena; Maschan, Michael; Maschan, Alexey; Novichkova, Galina; Olshanskaya, Yulia; Popov, Alexander
Abstract: It has long been known that there is a link between neuron glial antigen 2 (NG2) surface expression and KMT2A gene rearrangements in acute leukemia (AL). However, the exact levels of NG2 positivity that predict the presence of KMT2A rearrangement are not known. The current study focuses on a cohort of 505 pediatric AL patients who showed any level of positive NG2 expression (greater than 1% of cells) for whom comprehensive genetic data were available. NG2 expression was measured as either the percentage of positive cells or the number of molecules on the cell surface. KMT2A gene rearrangements were identified by FISH. The fusion partner was detected with RT‐PCR, LDI‐PCR or anchored multiplex PCR followed by high‐throughput sequencing. KMT2A ‐positive samples comprised a substantial proportion of the NG2‐positive cohort (180 of 505, 36%), with a total of 19 different types of translocation. Despite its occurrence in other AL genetic subgroups, NG2 expression was significantly increased in AL patients with KMT2A rearrangements in terms of both the cell percentage and number of molecules per cell. The threshold levels (TL) for NG2‐positivity were established by ROC analysis of the whole cohort and separately for children less than 1 years old and older with lymphoblastic (ALL) and myeloid (AML) leukemia. The lowest TL was defined in infants with ALL (7%), while in older children, the threshold was higher (12%). In AML patients, the situation was reversed, with 28% NG2‐positivity in infants and 14% in patients >1 year old. The defined TLs resulted in improved diagnostic performance compared to the conventional thresholds of 10% and 20% for all patient groups.